Alternative mode to Islamic home financing - Abdul Razak, Dzuljastri (Syed Hussain Publications Sdn. Bhd., 2009)
A Canadian-based cooperative is looking at forging a working relationship with a Malaysian cooperative to develop the musharakah mutanaqisah (diminishing partnership) mode for home financing. The initiative, discussed at a recent conference organised by the IIUM Institute of Islamic Banking and Finance (IIiBF), could possibly bring forward another venue for Islamic finance financing via the coperative movement. Dzuljastri Abdul Razak, a senior academic fellow at International Islamic University Malaysia's (IIUM) Kulliyah of Economics and Management Sciences discusses the issue.